Hedgehog threads to spread. - Briscoe, J.; Vincent, J.P. (Nature Cell Biology, 2013)
In vivo time-lapse imaging and functional tests bring fresh evidence that the morphogen Hedgehog is conveyed to target cells via long filopodia extensions, dubbed cytonemes. This study provides the tools and conceptual framework to understand how cytonemes form and carry morphogens.